A New Source of Mesenchymal Stem Cells for Articular Cartilage Repair: MSCs Derived From Mobilized Peripheral Blood Share Similar Biological Characteristics In Vitro and Chondrogenesis In Vivo as MSCs From Bone Marrow in a Rabbit Model. (March 2014) - Fu, Wei-Li; Zhou, Chun-Yan; Yu, Jia-Kuo
Background: Bone marrow (BM) has been considered as a major source of mesenchymal stem cells (MSCs), but it has many disadvantages in clinical application. However, MSCs from peripheral blood (PB) could be obtained by a less invasive method and be more beneficial for autologous transplantation than BM MSCs, which makes PB a promising source for articular cartilage repair in clinical use. Purpose: To assess whether MSCs from mobilized PB of New Zealand White rabbits have similar biological characteristics in vitro and chondrogenesis in vivo as BM MSCs. Study Design: Controlled laboratory study. Methods: A combined method of drug administration containing granulocyte colony stimulating factor (G-CSF) plus CXCR4 antagonist AMD3100 was adopted to mobilize the PB stem cells of adult New Zealand White rabbits in vitro. The isolated cells were identified as MSCs by morphological characteristics, surface markers, and differentiation potentials. A comparison between PB MSCs and BM MSCs was made in terms of biological characteristics in vitro and chondrogenesis in vivo. This issue was investigated from the aspects of morphology, immune phenotype, multiple differentiation capacity, expansion potential, antiapoptotic capacity, and ability to repair cartilage defects in vivo of PB MSCs compared with BM MSCs. Results: Peripheral blood MSCs were successfully mobilized by the method of combined drug administration, then isolated, expanded, and identified in vitro. No significant difference was found concerning the morphology, immune phenotype, and antiapoptotic capacity between PB MSCs and BM MSCs. Significantly, MSCs from both sources compounded with decalcified bone matrix showed the same ability to repair cartilage defects in vivo. For multipluripotency, BM MSCs exhibited a more osteogenic potential and higher proliferation capacity than PB MSCs, whereas PB MSCs possessed a stronger adipogenic and chondrogenic differentiation potential than BM MSCs in vitro. Conclusion: Although there are some differences in the proliferation and differentiation aspects between the 2 sources, PB MSCs share certain similar biological characteristics in vitro and chondrogenesis in vivo as BM MSCs. Clinical Relevance: These results suggest that PB MSCs are a new source of seed cells used in articular cartilage repair.